2014
DOI: 10.4161/23723548.2014.970955
|View full text |Cite
|
Sign up to set email alerts
|

The role of splicing factors in deregulation of alternative splicing during oncogenesis and tumor progression

Abstract: In past decades, cancer research has focused on genetic alterations that are detected in malignant tissues and contribute to the initiation and progression of cancer. These changes include mutations, copy number variations, and translocations. However, it is becoming increasingly clear that epigenetic changes, including alternative splicing, play a major role in cancer development and progression. There are relatively few studies on the contribution of alternative splicing and the splicing factors that regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 188 publications
1
37
1
1
Order By: Relevance
“…Changes in the nuclear level of regulators, including RBFOX2, hnRNP, and SR proteins, often occur in cancer ( Venables et al, 2009 ; Zhang and Manley, 2013 ). Although these changes frequently produce splice variants that affect cell cycle control, apoptosis, cell motility, and invasion, the molecular mechanisms that lead to these alterations and to specific downstream events that promote cancer remain largely unclear ( Zhang and Manley, 2013 ; Shilo et al, 2015 ). Another way to alter the activity of splicing regulators is through sequestration.…”
Section: Incapacitating the Regulatorsmentioning
confidence: 99%
“…Changes in the nuclear level of regulators, including RBFOX2, hnRNP, and SR proteins, often occur in cancer ( Venables et al, 2009 ; Zhang and Manley, 2013 ). Although these changes frequently produce splice variants that affect cell cycle control, apoptosis, cell motility, and invasion, the molecular mechanisms that lead to these alterations and to specific downstream events that promote cancer remain largely unclear ( Zhang and Manley, 2013 ; Shilo et al, 2015 ). Another way to alter the activity of splicing regulators is through sequestration.…”
Section: Incapacitating the Regulatorsmentioning
confidence: 99%
“…An important field of investigation is how dysregulation of splicing can be involved in cancerogenesis [258, 259]. Splicing defects in cancer cells can result from base-pair substitutions in splice sites or in splicing regulatory sequences.…”
Section: Formation and Export Of Mrnps Linked To Diseasementioning
confidence: 99%
“…More importantly, intricate splicing events are orchestrated by a limited number of SFs. Many studies have found links between the turbulences of SFs and the onset and progression of cancers (Cieply & Carstens, 2015;Shilo, Siegfried & Karni, 2015;Silipo, Gautrey & Tyson-Capper, 2015). In PAAD, SFs also exhibit potential effective functions in many ways.…”
Section: Introductionmentioning
confidence: 99%